2005
DOI: 10.1037/1099-9809.11.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Meaningful Spirituality for People of Color: Lessons for the Counseling Practitioner.

Abstract: This article attempts to capture a significant aspect of the counseling process for people of color: the spiritual dimension. It is argued that spirit and spirituality are relevant dimensions that should be integrated in counseling because spirituality is a key ingredient in the cultural upbringing and socialization of many people of color. Further, religious and spiritual beliefs are affected by experiences of racism and oppression, which then affects psychological coping. Reflective guidelines are offered to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 44 publications
1
68
0
Order By: Relevance
“…Walker and Dixon' s (2002) correlational study found a signifi cant relationship between academic success and reliance on a higher power among African American students. Latino students report greater levels of religious engagement (Campesino, Belyea, and Schwartz, 2009), and their spirituality and faith practices are linked with healthy psychological well-being (Cervantes and Parham, 2005). Levels of spirituality have been found to differ across ethnic groups (Parks, 2000); in our studies, spirituality also contributed differentially to student thriving.…”
Section: Pathways To Thriving: One Size Does Not Fit Allmentioning
confidence: 86%
“…Walker and Dixon' s (2002) correlational study found a signifi cant relationship between academic success and reliance on a higher power among African American students. Latino students report greater levels of religious engagement (Campesino, Belyea, and Schwartz, 2009), and their spirituality and faith practices are linked with healthy psychological well-being (Cervantes and Parham, 2005). Levels of spirituality have been found to differ across ethnic groups (Parks, 2000); in our studies, spirituality also contributed differentially to student thriving.…”
Section: Pathways To Thriving: One Size Does Not Fit Allmentioning
confidence: 86%
“…Although it is difficult to determine a precise definition of spirituality, it is often conceptualized as heightened awareness, consciousness, and connectedness with all beings (Cervantes & Parham, 2005) and with a universal being (Campesino & Schwartz, 2006), with beliefs existing on a continuum (Baez & Hernandez, 2001). Spirituality may take the form of religious faith or may be expressed through other means (Drench, Noonan, Sharby, & Ventura, 2007).…”
Section: Acculturation and Cultural Valuesmentioning
confidence: 99%
“…Within this larger context, social work and other helping professions have begun to explicitly include spirituality as a component of a As minority and other disempowered groups continue to enter treatment programs and join recovery groups in the United States, some authors posited that our understanding of substance abuse needs to be broadened to include the social conditions that are implicated in causing substance abuse problems by utilizing a socio-spiritual approach that incorporates spiritual and political worldviews (Morell, 1996). Cervantes and Parham (2005) reiterated this assertion by noting the importance of spirituality in the cultural tradition of people of color. They incorporated this political worldview notion by stating ''an assumption is made that these experiences of racism and discrimination have molded a spirituality of survival that has affected belief systems, sense of justice, prayer life, religious expectations, and so forth'' (Cervantes & Parham, 2005, p. 73).…”
Section: Introductionmentioning
confidence: 89%